2005
DOI: 10.1007/s00134-005-2845-4
|View full text |Cite
|
Sign up to set email alerts
|

The effect of N-acetylcysteine on posttraumatic changes after controlled cortical impact in rats

Abstract: Despite previously reported neuroprotective abilities of NAC, no positive effect on posttraumatic perfusion, brain edema formation, or contusion volume after focal brain injury was observed in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
28
1
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 38 publications
3
28
1
2
Order By: Relevance
“…These results correlate well with the literatures (Hicdonmez et al 2006;Rink et al 1995;Thomale et al 2006;Shapira et al 1988). In our study, the most consistent findings in histological sections of neuron regions amongst the TBI group involved severe degenerative changes, shrunken cytoplasma and extensively dark picnotic nuclei.…”
Section: Discussionsupporting
confidence: 93%
“…These results correlate well with the literatures (Hicdonmez et al 2006;Rink et al 1995;Thomale et al 2006;Shapira et al 1988). In our study, the most consistent findings in histological sections of neuron regions amongst the TBI group involved severe degenerative changes, shrunken cytoplasma and extensively dark picnotic nuclei.…”
Section: Discussionsupporting
confidence: 93%
“…In that study, no significant positive effect on posttraumatic perfusion, brain edema formation, or contusion volume after brain injury was observed at 24 h with the NAC (163 mg/kg) having been administered immediately as well as at 2 and 4 h after the trauma. However, they concluded that the tendency of a statistically non-significant diminished contusion volume after NAC treatment demonstrated the need for further investigation into the protective effects of neuronal survival on the cellular level [47]. Our results, however, do support the suggestion of Thomale et al in terms of neuronal survival.…”
Section: Discussioncontrasting
confidence: 58%
“…Thomale et al, however, observed no effect of NAC treatment on posttraumatic edema formation [47]. In a previous experimental study, Unterberg et al reported that the development of brain edema was of a cytogenic and vasogenic nature after the controlled cortical injury, while cytogenic edema formation predominated [61].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…27 However, in a study on rats with moderate left focal cortical contusion trauma, Thomale et al found that 163 mg/kg of NAC applied intraperitoneally 2-4 h after the brain injury was ineffective against post-traumatic perfusion, brain edema or contusion volume. 28 Cuzzocrea et al investigated the effect of NAC on brain ischemic injury in gerbils. Ischemia-reperfusion injury was induced in Mongolian gerbils by a single bilateral occlusion of the common carotid arteries, and NAC (20 mg/kg) was given intraperitoneally 30 min before and 1 h, 2 h, and 6 h after reperfusion.…”
Section: Discussionmentioning
confidence: 99%